Pengaruh Model Pembelajaran OME-AKE Berbantuan Media KAMIDO terhadap Minat Belajar SKI Siswa Kelas IV MIS Kajai Kabupaten Pasaman Barat - Aldo Patra Yunanda; Hidra Ariza (YASIN, 2026)
Learning interest is an important factor influencing the success of students’ learning process, but in learning Sejarah Kebudayaan Islam (SKI) at the elementary school level, students’ learning interest is still relatively low because the learning process tends to be conventional and has not yet utilized innovative learning models and media. This study aims to analyze the effect of implementing the OME-AKE learning model assisted by KAMIDO media on students’ learning interest in the subject of Islamic Cultural History (SKI). This study employed a quantitative approach with a pre-experimental design in the form of a one-group pretest-posttest design. The study involved 30 fourth-grade students of MIS Kajai, West Pasaman Regency, selected using purposive sampling. Data were collected through observation and a learning interest questionnaire administered before and after the treatment, and were then analyzed using inferential statistics through a paired sample t-test with the assistance of SPSS. The results showed that the implementation of the OME-AKE learning model assisted by KAMIDO media significantly increased students’ learning interest, as indicated by an increase in the mean score from 82.27 on the pretest to 101.37 on the posttest, with a significance value of 0.000 (p < 0.05). These findings indicate that the implementation of an active learning model combined with creative learning media is able to increase students’ engagement and learning interest. Thus, this study contributes to the development of innovative learning strategies in elementary education and provides practical implications for teachers in designing learning that is more interactive, engaging, and meaningful for students.